A Genome-Wide Analysis of Clinical Chorioamnionitis among Preterm Infants - Spiegel, Ariana M.; Li, Jingjing; Oehlert, John W.; Mayo, Jonathan A.; Quaintance, Cecele C.; Girsen, Anna I.; Druzin, Maurice L.; El-Sayed, Yasser Y.; Shaw, Gary M.; Stevenson, David K.; Gibbs, Ronald S. (American Journal of Perinatology, 2019)
Objective To identify single nucleotide polymorphisms (SNPs) associated with clinical chorioamnionitis among preterm infants.Study Design We reanalyzed a genome-wide association study (GWAS) from preterm newborns at less than 30 weeks' gestation. Cases and control definitions were determined using administrative records. There were 213 clinical chorioamnionitis cases and 707 clinically uninfected controls. We compared demographic and clinical outcomes of cases and controls. We performed a GWAS and compared the distribution of SNPs from the background genes and from the immunome genes. We used a Wilcoxon's rank-sum test to compare the SNPs normalized odds ratio and used odds ratios and p-values to determine candidate genes.Results Infants affected by clinical chorioamnionitis were more likely to have periventricular leukomalacia, high-grade retinopathy, and high-grade intraventricular hemorrhage (IVH). Although a GWAS did not identify SNPs associated with clinical chorioamnionitis at the genome-wide significance level, a direct test on the exonic variants in the human immunome revealed their significant increase of risk in clinical chorioamnionitis.Conclusion Among very preterm infants, clinical chorioamnionitis was associated with periventricular leukomalacia, high-grade retinopathy, and IVH. Our analysis of variants in the human immunome indicates an association with clinical chorioamnionitis in very preterm pregnancies.
Keywords: candidate gene; analysis; clinical chorioamnionitis; genome-wide association study; preterm birth